Case Report: Rectal Perforation Secondary to a Toothbrush in an Elderly Man - Aimanan, Karthigesu; Lim, Soon Yee; Ahmad Hamidi, Ahmad Junaidi; Chieng, Tiong How; Hayati, Firdaus (Frontiers in Surgery, 2022)
Rectal foreign bodies often pose a challenging diagnostic and management dilemma. A 72-year-old gentleman who is mentally sound was brought to the emergency department for severe epigastric pain of a 1-week duration. On examination, he was pyrexial and in sepsis. The abdomen was guarded. A digital rectal examination was normal. Erect chest radiography revealed air under the diaphragm and abdominal radiography showed neither dilated bowel nor foreign body. A diagnostic laparoscopy was performed which revealed a yellow hard rod-shaped foreign body at the pelvis. Upon conversion to midline laparotomy, the foreign body was found to be a toothbrush with intraperitoneal rectal perforation of 1cm in length. The brush was removed and the perforation was repaired primarily. A diverting transverse loop colostomy was created. Rectal foreign bodies may cause life-threatening rectal injuries including lacerations, bleeding, perforation, and obstruction. An orderly approach is essential for the diagnosis, management, and post-extraction evaluation of the patient with a rectal foreign body.